2022
DOI: 10.3390/separations9050110
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Fe3+ on Flotation Separation of Feldspar and Epidote with Sodium Oleate at Natural pH

Abstract: The most common beneficiation method for feldspar is flotation with a cationic (amine) collector under acidic conditions. However, there are several disadvantages to this, such as environmental pollution and equipment corrosion. In order to resolve such problems, it is important to study the flotation of feldspar using anionic collectors under natural pH conditions. The purpose of this paper is to study the effects and mechanism of Fe3+ on flotation separation of feldspar and epidote using sodium oleate (NaOL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Espiritu et al (2019) also used DFT simulation to study the effect of dissolved ions in dolomite on the flotation of monazite, and found that Ca 2+ and Mg 2+ ions reduced the floatability of monazite due to the adsorption of calcium carbonate or magnesium hydroxide on monazite and the precipitation of calcium or magnesium oleate. and Zeng et al (2022) found that adding a small amount of Fe 3+ to the pulp before SOH can significantly improve the flotation of fine monazite. This is because the addition of Fe 3+ promotes the adsorption of SOH and greatly improves the hydrophobicity of the surface of monazite.…”
Section: Introductionmentioning
confidence: 99%
“…Espiritu et al (2019) also used DFT simulation to study the effect of dissolved ions in dolomite on the flotation of monazite, and found that Ca 2+ and Mg 2+ ions reduced the floatability of monazite due to the adsorption of calcium carbonate or magnesium hydroxide on monazite and the precipitation of calcium or magnesium oleate. and Zeng et al (2022) found that adding a small amount of Fe 3+ to the pulp before SOH can significantly improve the flotation of fine monazite. This is because the addition of Fe 3+ promotes the adsorption of SOH and greatly improves the hydrophobicity of the surface of monazite.…”
Section: Introductionmentioning
confidence: 99%
“…Solution chemistry calculations and adsorption measurements reveal that, in the flotation process of sodium feldspar, Fe 3+ ions bind to the feldspar surface as ferric hydroxide. Moreover, the Fe 3+ can modify the metallic bond characteristics of the feldspar surface, thereby facilitating the adsorption of sodium oleate (NaOL) onto the mineral surface via its carboxylate groups (Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%